Investigation of the effect of CNTs on the mechanical properties of LPET/glass fiber thermoplastic composites. (December 2020) - Demircan, O; Al-darkazali, A; İnanç, İ; Eskizeybek, V
Within this research, four kinds of multiwalled carbon nanotubes (MWCNTs; 0.0, 0.7, 0.9, and 1.1 wt%) integrated thermoplastic composites with commingled yarns (low melting point polyethylene terephthalate fiber/glass fiber) were fabricated using hot-press machine. The fabricated composites were tested against tensile and three-point flexural loadings. Specimens with 0.9-wt% MWCNTs in 90° direction showed the highest values of tensile and flexural properties with an improvement of about 7% and 33% in tensile and flexural modulus and about 3% and 65% in tensile and flexural strength compared to specimens without MWCNTs in 90° direction. This improvement can most likely be attributed to an increase in interfacial adhesion due to the presence of the carbon nanotubes.